Alarelin active immunization influences expression levels of GnRHR, FSHR and LHR proteins in the ovary and enhances follicular development in ewes. (26th February 2013) - Wei, Suocheng; Chen, Shien; Gong, Zhuandi; Ouyang, Xiahui; An, Lifeng; Xie, Kun; Dong, Jiangling; Wei, Min
Abstract We investigated the effects of gonadotropin releasing hormone (GnRH) agonist on expressions of GnRH receptor (GnRHR), follicle‐stimulating hormone receptor (FSHR) and luteinizing hormone receptor (LHR) proteins in the ovaries and follicular development in the ewes. Forty‐two pre‐pubertal ewes were assigned to experimental groups 1 to 5 (EG‐I to EG‐V) and control group (CG). Ewes in EG‐I, EG‐II and EG‐III were subcutaneously injected with 200, 300 or 400 μg alarelin antigens twice (on days 0 and 14), respectively. Ewes in EG‐IV and EG‐V were subcutaneously injected with 200 μg and 300 μg alarelin antigen four times (on days 0, 7, 14 and 21). Ewes in CG were subcutaneously injected with a solvent twice (on days 0 and 14). Serum concentrations of GnRH antibody in the EGs increased and were higher than (P < 0.05) that of CG from day 14 to day 60. GnRH antibody concentrations in EG‐IV and EG‐V were higher than that in EG‐I, EG‐II and EG‐III from days 35 to 45. Expressions of GnRHR protein in EG‐IV and EG‐V were lower than that in CG (P < 0. 01). Expressions of FSHR and LHR proteins in EGs increased. Levels of FSHR and LHR proteins in EG‐IV and EG‐V (P < 0.05) were higher than CG. Ovarian weights in EGs increased. Values of follicle vertical diameter, follicle transverse diameter, follicle wall thickness, follicle externatheca thickness and follicle internatheca thickness in EG‐III and EG‐V were greater than other groups. Primordial follicles and primary follicles developed quickly in alarelin‐immunized animals. Secondary follicles and mature follicles became more abundant. Mitochondria, mitochondrial cristaes and cortical granules increased. Serum FSH concentrations of EGs remained higher than that in CG from days 28 to 70 (P < 0.05). Alarelin immunization stimulated GnRH antibody production, suppressed expression of GnRHR protein, enhanced expressions of FSHR and LHR proteins in ovaries, promoted FSH secretion and thereby accelerated the development of ovaries and follicles in ewes.